Subcutaneous Implants of Buprenorphine-Cholesterol-Triglyceride Powder in Mice. (27th November 2014) - DeTolla, L.; Sanchez, R.; Khan, E.; Tyler, B.; Guarnieri, M.
Abstract : Subcutaneous drug implants are convenient systems for the long-term delivery of drugs in animals. Lipid carriers are logical tools because they generally allow for higher doses and low toxicity. The present study used an US Food and Drug Administration Target Animal Safety test system to evaluate the safety of a subcutaneous implant of a cholesterol-triglyceride-buprenorphine powder in 120 BALB/c mice. Mice were evaluated in 4- and 12-day trials with 1- and 5-fold doses of the intended 3 mg/kg dose of drug. One male mouse treated with three 3 mg/kg doses and surgery on days 0, 4, and 8 died on day 9. The cause of death was not determined. In the surviving 119 mice there was no evidence of skin reaction at the site of the implant. Compared to control animals treated with saline, weight measurements, clinical pathology, histopathology, and clinical observations were unremarkable. These results demonstrate that the lipid carrier is substantially safe. Cholesterol-triglyceride-drug powders may provide a valuable research tool for studies of analgesic and inflammatory drug implants in veterinary medicine.